2012
DOI: 10.1038/aja.2011.104
|View full text |Cite
|
Sign up to set email alerts
|

Muscle function, physical performance and body composition changes in men with prostate cancer undergoing androgen deprivation therapy

Abstract: Prostate cancer (PCa) is the most common visceral malignancy in men with androgen deprivation therapy (ADT) the preferred therapy to suppress testosterone production and hence tumor growth. Despite its effectiveness in lowering testosterone, ADT is associated with side effects including loss of muscle mass, diminished muscle strength, decrements in physical performance, earlier fatigue and declining quality of life. This review reports a survey of the literature with a focus on changes in muscle strength, phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 129 publications
6
47
2
1
Order By: Relevance
“…In support of our limitations when muscle strength was assessed, 40% of men in a cohort of 62 men commencing ADT (mean age, 68 years) were unable to complete at least one of three assessment of handgrip strength over a 12-month follow-up [28] . Moreover, given the average annual gain of total body fat mass exceeds 11% in ADT-treated men [198] and the known limitations of DXA scan acquisition in those with obesity [76] , the missing 186 Chapter 6 data in our study appears to be in line with current limitations of these tools. However, our findings suggest that researchers should consider the feasibility of data collection when designing trials with clinical populations groups with multiple comorbidities, such as men treated with ADT for PCa.…”
Section: Data Collectionsupporting
confidence: 61%
See 2 more Smart Citations
“…In support of our limitations when muscle strength was assessed, 40% of men in a cohort of 62 men commencing ADT (mean age, 68 years) were unable to complete at least one of three assessment of handgrip strength over a 12-month follow-up [28] . Moreover, given the average annual gain of total body fat mass exceeds 11% in ADT-treated men [198] and the known limitations of DXA scan acquisition in those with obesity [76] , the missing 186 Chapter 6 data in our study appears to be in line with current limitations of these tools. However, our findings suggest that researchers should consider the feasibility of data collection when designing trials with clinical populations groups with multiple comorbidities, such as men treated with ADT for PCa.…”
Section: Data Collectionsupporting
confidence: 61%
“…Previous studies in men treated with ADT have reported mixed results in terms of muscle strength when compared to both PCa and healthy controls [198] . Consistent with our findings, Joly et al [26] reported no difference in handgrip strength between 57 men treated with ADT (mean age, 73 years) and 51 healthy age-matched controls.…”
Section: Effects Of Androgen Deprivation Therapy On Muscle Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapy for PC often promotes loss of muscle mass, diminished muscle strength, increases fat mass and central adiposity, improving the loss of physical performance and earlier fatigue [28] [29]. These findings may explain worse HRQoL, affecting particularly the physical function and the fatigue symptom.…”
Section: Hrqol Prospective Evolution Analysis Along Five Years Since mentioning
confidence: 99%
“…The studies of the effects of ADT on muscle mass, muscle strength, and physical performance have yielded variable results and are summarized below. Well-designed, controlled, prospective studies in this area are lacking (Storer et al 2012). Muscle mass decreases consistently; however, when muscle strength outcomes are assessed, results have not all been concordant.…”
Section: Muscle Effects Of Adtmentioning
confidence: 99%